Beneficios del sistema de compensación para la motivación del personal administrativo de una empresa privada comercializadora de materiales de construcción de la ciudad de Quito - Peñaherrera Arcos, Vanessa Grisel (2017)
The present study of qualitative focus and descriptive reach has as an objective to identify the benefits of the compensation system that generates more motivation to the administrative staff in a material construction company in Quito city. The method of collection of data used for this study will be a semistructured interview for each person in the administrative area of the company, with the goal of getting value information that allows the analysis of their human motivations, based on this judgment, to set the benefits that generate more motivation for the compensation system. There is a limited study about the benefits to motivate the staff if you compare with other studies about other factors that influence of the motivation of the workforce of an organization. However in this study we can see thy benefits that are part of the compensation system are very important for the motivation of the work force giving then welfare, personal and professional development. As an Organizational Psychologist is our responsibility to generate value for our workforce and for the company with our input.